HUBUNGAN ANTARA PENGETAHUAN DAN TINGKAT STRES TERHADAP KAMBUH ULANG GASTRITIS DI WILAYAH KERJA PUSKESMAS KOTA SUNGAI PENUH TAHUN 2018 - Monica, Thrisia (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
Recurrence rates occurring in gastritis sufferers often develop uluhati pain accompanied by nausea and vomiting and decreased appetite, especially in patients with less knowledge of gastritis, such as irregular eating patterns that consume spicy foods and mengadung acidic substances that cause increased acid reflux. From WHO data the incidence of gastritis is about 1.8 - 2.1 million. In Indonesia 274-396 cases. In the province of jambi 8.74%. At the river health clinic full of 119 cases. The purpose of this research is to know the correlation between knowledge and stress level to recurrence of gastritis in Working Area of Pukesmas Sungai Penuh in 2015. The type of this research is Analytical survey Using cross sectional design implemented in Work Area of Pukesmas Sungai Penuh in August. The population of this study were residents who experienced a recurrence of gastritis in the Working Area of Pukesmas Sungai Penuh from 01 February to 28 February 2015 of 38 respondents. Samples are taken by accident sampling with the respondent takers who happen to exist or are available. Data collection by interview using questioner. Data processing techniques starting from editing, coding, entry, and cleaning. Univariate analysis with descriptive statistics and bivariate analysis using Chi-Square statistical test. Bivariate analysis was found to have a significant relationship between the level of knowledge on recurrence of gastritis with p value 0.032, and there is a significant relationship between stress levels on recurrence of gastritis with p value 0.020. It is expected that the efforts of the head of Pukesmas Sungai Penuh and other health workers to reduce the number of recurrence of gastritis that occurs in the community, by providing health promotion to patients about relapse gastritis. Keywords: relationship, knowledge, stress, gastritis